2007
DOI: 10.1186/1472-6793-7-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory network of inflammation downstream of proteinase-activated receptors

Abstract: BackgroundProtease-activated receptors (PAR) are present in the urinary bladder, and their expression is altered in response to inflammation. PARs are a unique class of G protein-coupled that carry their own ligands, which remain cryptic until unmasked by proteolytic cleavage. Although the canonical signal transduction pathway downstream of PAR activation and coupling with various G proteins is known and leads to the rapid transcription of genes involved in inflammation, the effect of PAR activation on the dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 94 publications
(108 reference statements)
1
28
0
Order By: Relevance
“…The induction of Wnts has been only poorly described in inflammatory settings: to date, an upregulation of Wnt6 has been almost exclusively observed in microarray-based studies, for example, in M. tuberculosis-infected murine macrophages (46), in the bladder of mice after stimulation with LPS, in a rat renal allograft model, in coloscopic biopsies of ulcerative colitis patients, and most recently also in the lung of asthma patients (14,(47)(48)(49). Of note, Liu et al (50) describe an induction of Wnt6 mRNA by Salmonella typhimurium infection of murine intestinal epithelia cells ex vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of Wnts has been only poorly described in inflammatory settings: to date, an upregulation of Wnt6 has been almost exclusively observed in microarray-based studies, for example, in M. tuberculosis-infected murine macrophages (46), in the bladder of mice after stimulation with LPS, in a rat renal allograft model, in coloscopic biopsies of ulcerative colitis patients, and most recently also in the lung of asthma patients (14,(47)(48)(49). Of note, Liu et al (50) describe an induction of Wnt6 mRNA by Salmonella typhimurium infection of murine intestinal epithelia cells ex vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to inoculation of mouse bladders, we quantified the amount of LPS in our CNF1 preparation because LPS itself elicits a robust inflammatory response that could potentially confound interpretation of our results. We found that the CNF1 preparation contained 9.9 ng/ml LPS, a concentration that is 10,000-fold lower than the concentration of LPS (100 g/ml) that is typically introduced into the bladder to stimulate an inflammatory response (59,60). We inoculated 12 mice per group intraurethrally with 1 or 2 g CNF1 and sacrificed them 24 h later.…”
Section: Resultsmentioning
confidence: 99%
“…To assess alterations in the receptor expression, we used chromatin immunoprecipitation (ChIP) combined with quantitative real-time PCR (Q-PCR), a method that uses the DNA transcriptome and, therefore, reflects transcription of active genes (37,40,41). Although we detected statistically significant inflammation-induced increase in the expression of some VEGF receptors and coreceptors, the changes were too small to be considered consequential (Fig.…”
Section: Chip-q-pcr Assessment Of Vegf Signaling In Bladder Inflammationmentioning
confidence: 99%
“…In normal bladder this signaling is a key mechanism downstream of protease-activated receptor (PARs) activation in response to proinflammatory stimuli (36,40), while in bladder with the superficial cancer it is part of the response to intravesical therapy with Bacillus Calmette-Guerin (BCG) (34). This new appreciation of VEGF's signaling role in bladder inflammation is supported by emerging evidence that levels of various VEGF proteins are, in general, increased at the site of inflammation (20,26,27,35,49) and that infiltrating lymphocytes and other inflammatory cells represent an additional source of VEGF (24,27).…”
mentioning
confidence: 99%